Elements of Pedestrian Pathways and Their Influence on Pedestrian Comfort: A Literature Review - Monica, Silvira (Rifa'Institute, 2026)
Introduction: Pedestrian pathways are an essential element of urban transportation systems that support active mobility and environmental sustainability. However, the quality of pedestrian pathways in many urban areas has not fully addressed pedestrian comfort, both in terms of environmental and physical aspects. Objective: This article aims to review pedestrian pathway elements and their influence on pedestrian comfort in urban environments. Method: This study employs a literature review method using a thematic analysis approach of national and international scientific articles published between 2020 and 2025. Results and Discussion: The review findings indicate that environmental elements, particularly vegetation and microclimatic conditions, are the most dominant factors influencing pedestrian comfort. In addition, physical characteristics of pedestrian pathways, safety aspects, and psychological comfort also play important roles in shaping walking experiences. Conclusion: Pedestrian comfort is multidimensional and influenced by interactions among environmental, physical, and perceptual elements. Therefore, integrated pedestrian pathway planning that emphasizes environmental quality is required to enhance pedestrian comfort and support urban sustainability.